The killer prince? MBS and the chilling special operation to assassinate Washington Post journalist Jamal Khashoggi by Saudi forces - Wilson, Owen (Gibson Sqaure, 2021)
On 2 October 2018, Jamal Khashoggi, a Washington Post journalist, was lured into the Saudi diplomatic mission in Istanbul, dismembered in fifteen parts and packed into five suitcases. Astonishingly, a forensic UN report concluded nine months later there was 'credible evidence' that the Crown Prince of Saudi Arabia was responsible for the killing. Earlier, Donald Trump issued a shocking statement that 'It could very well be that the crown prince had knowledge of this'. It followed the CIA's assessment of Saudi Arabia's de-facto ruler that, 'there is no way this happened without him being aware or involved.' Crime writer Owen Wilson has forensically gathered all the known facts about the slaughter and the reasons so that the reader can make up their own mind. --
Keywords: Ḫāšquǧī, Ǧamāl Aḥmad -- 1958-2018; Āl-Saʿūd, Muḥammad Ibn-Saʿd Ibn-ʿAbd-ar-Raḥmān; The Washington Post; Geschichte 2018-2022; Mord; Diplomatische Beziehungen; USA; Saudi-Arabien; Āl Saʻūd, Muḥammad bin Salmān bin ʻAbd al-ʻAzīz / Crown Prince of Saudi Arabia / 1985-; Khāshqujī, Jamāl Aḥmad / 1958-2018; Āl Saʻūd, House of; Saudi Arabia / Politics and government / 21st century; Saudi Arabia / Foreign relations / 21st century; State crimes / Saudi Arabia / History / 21st century; Diplomatic relations; Politics and government; State crimes; Saudi Arabia; 2000-2099; Biographies; History